2019
DOI: 10.3389/fpsyg.2019.01725
|View full text |Cite
|
Sign up to set email alerts
|

Forgiving Adolescents: Far From Depression, Close to Well-Being

Abstract: Forgiveness has been proven to be an effective way of regulating negative affect and decreasing depression. This study aimed at examining the relationship among constructs particularly relevant to adolescents’ well-being, including forgivingness (dispositional forgiveness) anger, depression and Hedonic Balance (HB). Specifically, using a structural equation modelling approach, the fully mediational role of the different facets of anger in the relationship between forgiveness and depression was tested in 773 ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…Moreover, the authors found that resilience was a good predictor of well-being. Finally, resilience was negatively correlated with distress (Panchal et al, 2016) and positively predicted humility, gratitude and forgiveness (Baldwin, Jackson, Okon, & Cannon, 2011), variables of effective coping with stressful situations in life and of positive adjustment (Barcaccia, Pallini, Milioni, & Vecchio, 2018;Barcaccia et al, 2019). Strengthening egoresiliency can help vulnerable individuals to better manage stress and can promote higher levels of adaptive coping.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the authors found that resilience was a good predictor of well-being. Finally, resilience was negatively correlated with distress (Panchal et al, 2016) and positively predicted humility, gratitude and forgiveness (Baldwin, Jackson, Okon, & Cannon, 2011), variables of effective coping with stressful situations in life and of positive adjustment (Barcaccia, Pallini, Milioni, & Vecchio, 2018;Barcaccia et al, 2019). Strengthening egoresiliency can help vulnerable individuals to better manage stress and can promote higher levels of adaptive coping.…”
Section: Discussionmentioning
confidence: 99%
“…Consider that forgiveness has been shown to be positively associated with many beneficial constructs: psychological well-being ( Karremans et al, 2003 ; Pareek et al, 2016 ; Akhtar and Barlow, 2018 ; Barcaccia et al, 2019 ), physical health ( Lee and Enright, 2019 ), decreased blood pressure for both victim and perpetrator ( Hannon et al, 2010 ), greater health resilience ( Worthington and Scherer, 2004 ), increased longevity [e.g., Barcaccia et al (2020) ; see Witvliet et al (2001) ], and reduced depression ( Toussaint et al, 2012 ). It is also important to consider, however, that forgiveness may not always be the ideal outcome following a transgression.…”
Section: Future Research and Limitationsmentioning
confidence: 99%
“…Finally, an area that deserves further exploration regards the moderator effect of protective factors in the relation between life events and crime type. It would be interesting to examine whether certain protective factors such as the capacity to forgive oneself ( Barcaccia et al, 2019 ) could protect the individual from the criminal behavior.…”
Section: Discussionmentioning
confidence: 99%